Faktor-faktor yang berhubungan dengan persepsi body image pada tenaga kesehatan di RSUD Meuraxa - Alfian Alfian; Asnawi Abdullah; Nurjannah Nurjannah (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Body image reflects a person's health status, for health workers body image can describe professionalism. Health workers should be able to give a role models for hospital visitors in the health sector, especially in maintaining optimal body image.Objectives: This study aims to determine the factors associated with the perception of body image in health workers at Meuraxa Hospital, Banda Aceh City.Methods: This research was conducted by analytic descriptive with cross-sectional design. Data were collected using a questionnaire. The population in this study were all health workers at Meuraxa Hospital, amounting to 375 people. The sample size was taken based on the provisions of Krejcie and Morgan's statutory table, as many as 191 people. The statistical test used was logistic regression and was analyzed using the stata 14.Results: Perceptions of negative body image were more common in women (64.10%), and at the age of 25-29 years (70.18%). Factors related to the body image of health workers were gender (p= 0.004), food consumption behavior (p= 0.001), interpersonal relationships (p= 0.021). Meanwhile, age and medical conditions did not show a relationship with body image. The dominant factor causing body image is consumption behavior.Conclusion: The factors related to the body image of health workers are gender, food consumption behavior, and interpersonal relationships. While the dominant factor is food consumption behavior.